International consensus on minimum preclinical testing requirements for the development of innovative therapies for children and adolescents with cancer - Vassal, Gilles; Houghton, Peter J.; Pfister, Stefan; Smith, Malcolm A.; Caron, Huib N.; Li, Xiao-Nan; Shields, David J.; Witt, Olaf; Molenaar, Jan J.; Colombetti, Sara; Schüler, Julia; Stancato, Lou F. (Molecular cancer therapeutics, 2021)
Cancer remains the leading cause of disease-related death in children. For the many children who experience relapses of their malignant solid tumors, usually after very intensive first-line therapy, curative treatment options are scarce. Preclinical drug testing to identify promising treatment elements that match the molecular make-up of the tumor is hampered by the fact that (i) molecular genetic data on pediatric solid tumors from relapsed patients and thus our understanding of tumor evolution and therapy resistance are very limited to date and (ii) for many of the high-risk entities, no appropriate and molecularly well-characterized patient-derived models and/or genetic mouse models are currently available. However, recent regulatory changes enacted by the European Medicines Agency (class waiver changes) and the maturation of the RACE for Children act with the FDA, will require a significant increase in preclinical pediatric cancer research and clinical development must occur. We detail the outcome of a pediatric cancer international multistakeholder meeting whose output aims at defining an international consensus on minimum preclinical testing requirements for the development of innovative therapies for children and adolescents with cancer. Recommendations based on the experience of the NCI funded PPTP/C (www.ncipptc.org) and the EU funded ITCC-P4 public private partnership (www.itccp4.eu) are provided for the use of cell-based and mouse models for pediatric solid malignancies, as well as guidance on the scope and content of preclinical proof-of-concept data packages to inform clinical development dependent on clinical urgency. These recommendations can serve as a minimal guidance necessary to jumpstart preclinical pediatric research globally.